2009
DOI: 10.1186/1471-2407-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress and intracellular glutathione in the sensitivity to apoptosis induced by proteasome inhibitor in thyroid cancer cells

Abstract: BackgroundThe proteasome inhibitor bortezomib has shown impressive clinical activity alone and in combination with conventional and other novel agents for the treatment of multiple myeloma (MM) and some solid cancers. Although bortezomib is known to be a selective proteasome inhibitor, the downstream mechanisms of cytotoxicity and drug resistance are poorly understood.MethodsProteasome activity, intracellular glutathione (GSH) and ROS levels, as well as activities of GSH synthesis enzymes were measured using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 34 publications
3
60
0
2
Order By: Relevance
“…We found that proteasome activity is increased in malignant cells derived from different types of cancer as compared with normal cells [20] , indi- Although it has been reported that nontoxic proteasome inhibition protected cells from oxidative stress [21] , our results showed that proteasome inhibitor MG-132 at toxic concentrations could generate oxidative stress and induce apoptosis in glioma cells. Oxidative stress has been demonstrated to be closely associated with cellular death in various tumor cells [9,16,22] . Studies investigating the relationship between oxidative stress and apoptosis have indicated that oxidative stress may be a precursor to apoptosis in C6 glioma cells [23,24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that proteasome activity is increased in malignant cells derived from different types of cancer as compared with normal cells [20] , indi- Although it has been reported that nontoxic proteasome inhibition protected cells from oxidative stress [21] , our results showed that proteasome inhibitor MG-132 at toxic concentrations could generate oxidative stress and induce apoptosis in glioma cells. Oxidative stress has been demonstrated to be closely associated with cellular death in various tumor cells [9,16,22] . Studies investigating the relationship between oxidative stress and apoptosis have indicated that oxidative stress may be a precursor to apoptosis in C6 glioma cells [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, proteasome inhibition has protective effects on vascular cells undergoing oxidative stress [14] . Even for tumor cells, proteasome inhibition also has varied effects on the production of ROS in different thyroid cancer cell lines [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies related to thyroid cancer have reported that apoptotic cell death of ATC FRO cells by PsL5F was mediated via upregulated ROS (Liu et al 2009). The production of ROS has also been associated with bortezomibinduced apoptosis in thyroid cancer cells (Du et al 2009). Moreover, 15-deoxy-delta12,14-prostaglandin J2 is cytotoxic via intracellular ROS in cells of the CG3 thyroid papillary cancer cell line (Chen et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…and 14.) is needed, as the genotoxic effect of arsenic metabolites is not only dependent on its oxidative state but also on the state of methylation Dopp et al, 2010b). Wnek et al (2009) reported that in UROtsa cells DNA damage caused by MMA(III) is not only a phenomenon of acute treatment but also an important effect in chronic, low-level exposure for 12 -52 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of arsenic is of great importance for toxicological studies. As summarised by Dopp et al (2010b) and , the cyto-and genotoxic effects are highly dependent on the particular arsenic species, its cellular uptake, and its intracellular metabolism. For example, the toxicity of MMA(III) is 20 times greater than that of As(III) (Styblo et al, 2002;Bredfeldt et al, 2006 Fig.…”
Section: Introductionmentioning
confidence: 99%